Immunity following SARS-CoV-2 vaccination in autoimmune neurological disorders treated with rituximab or ocrelizumab - Nytrova, Petra; Stastna, Dominika; Tesar, Adam; Menkyova, Ingrid; Posova, Helena; Koprivova, Helena; Mikulova, Veronika; Hrdy, Jiri; Smela, Gabriela; Horakova, Dana; Rysankova, Irena; Doleckova, Kristyna; et al. (Frontiers in Immunology, 2023)
Background: Rituximab (RTX) and ocrelizumab (OCR), B cell-depleting therapy targeting CD20 molecules, affect the humoral immune response after vaccination. How these therapies influence T-cell-mediated immune response against SARS-CoV-2 after immunization remains unclear. We aimed to evaluate the humoral and cellular immune response to the COVID-19 vaccine in a cohort of patients with multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD), and myasthenia gravis (MG). Methods: Patients with MS (83), NMOSD (19), or MG (7) undergoing RTX (n=47) or OCR (n=62) treatment were vaccinated twice with the mRNA BNT162b2 vaccine. Antibodies were quantified using the SARS-CoV-2 IgG chemiluminescence immunoassay, targeting the spike protein. SARS-CoV-2-specific T-cell responses were quantified by interferon γ release assays (IGRA). The responses were evaluated at two different time points (4-8 weeks and 16-20 weeks following the 2nd dose of the vaccine). Immunocompetent vaccinated individuals (n=41) were included as controls. Results: Almost all immunocompetent controls developed antibodies against the SARS-CoV-2 trimeric spike protein, but only 34.09% of the patients, without a COVID-19 history and undergoing anti-CD20 treatment (via RTX or OCR), seroconverted. This antibody response was higher in patients with intervals of longer than 3 weeks between vaccinations. The duration of therapy was significantly shorter in seroconverted patients (median 24 months) than in the non-seroconverted group. There was no correlation between circulating B cells and the levels of antibodies. Even patients with a low proportion of circulating CD19+ B cells (<1%, 71 patients) had detectable SARS-CoV-2 specific antibody responses. SARS-CoV-2 specific T cell response measured by released interferon γ was detected in 94.39% of the patients, independently of a humoral immune response. Conclusions: The majority of MS, MG, and NMOSD patients developed a SARS-CoV-2-specific T cell response. The data suggest that vaccination can induce SARS-CoV-2-specific antibodies in a portion of anti-CD20 treated patients. The seroconversion rate was higher in OCR-treated patients compared to those on RTX. The response represented by levels of antibodies was better in individuals, with intervals of longer than 3 weeks between vaccinations.